Each tiny spark - Cartaya, Pablo (Puffin Books, 2020)
Emilia Torres thought her life would return to normal when Dad returned from deployment, but instead she finds it unraveling. Dad shuts himself off from Emilia and her mom and abuela, spending his time working on his classic car. One day, though, Dad invites her in to help him work, and begins teaching Emilia how to weld. Unfortunately, at the same time, one of her classmates, her best friend Gus, finds himself in the middle of a community-rupturing conflict.